ANALISIS PELAKSANAAN PENDIDIKAN INKLUSI DI KECAMATAN MIJEN,SEMARANG: PRAKTIK, TANTANGAN DAN STRATEGI SEKOLAH DASAR NEGERI KEDUNGPANE 02 - Wulandari, Dyah Ayu; Kamila, Adinda Zulfa; Sabrina, Amel Putri; Rahmawati, Aulia; Wijayanti, Dyah Nuri; Khasanah, Putri Yatun; Tinadi, Silvy Felecia Putri; Azzahro, Shafira; Nur Khalimah, Zahrotun Siti; Anindita, Fayaza Aqila; Ratnaningrum, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide a comprehensive overview of the implementation of inclusive education at SD Negeri Kedungpane 02, Mijen District, Semarang. Inclusive education is a crucial effort to achieve educational equity and justice for all children, including those with special needs (children with disabilities). The research employs a qualitative case study approach, utilizing observation, in-depth interviews, and documentation with the principal and homeroom teachers as primary data sources. The findings indicate that the implementation of inclusive education at SD Negeri Kedungpane 02 still faces several challenges, such as limited resources, teacher readiness, and insufficient supporting facilities. Furthermore, teachers’ understanding of the diverse characteristics of inclusive students is pivotal in determining effective teaching strategies. The registration process for inclusive students at this school is relatively transparent but still requires improvements to be more accessible for children with special needs and their families. The curriculum applied is adaptive and flexible, yet its implementation needs further support from various stakeholders. The study recommends enhancing teacher competencies, providing adequate facilities, and strengthening collaboration among schools, parents, and the community. This research is expected to serve as a reference for other elementary schools in developing high-quality and equitable inclusive education.